2003
DOI: 10.1002/cne.10541
|View full text |Cite
|
Sign up to set email alerts
|

Differential morphology of pyramidal tract‐type and intratelencephalically projecting‐type corticostriatal neurons and their intrastriatal terminals in rats

Abstract: Two types of corticostriatal projection neurons have been identified: 1) one whose intrastriatal arborization arises as a collateral of a projection to the ipsilateral brainstem via the pyramidal tract (PT-type); and 2) one that projects intratelencephalically to the cortex and striatum, in many cases bilaterally, but not extratelencephalically (IT-type). To assess possible functional differences between these two neuron types, we characterized their laminar location in the cortex, their perikaryal size, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
211
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(226 citation statements)
references
References 103 publications
(218 reference statements)
13
211
2
Order By: Relevance
“…Direct pathway cells are considered to promote desired movements, and GPe-exclusive cells are considered to inhibit unwanted movement (Albin et al, 1989;DeLong, 1990;Lei et al, 2004). Recently, it has been revealed that two types of corticostriatal cells differentially innervate one of the above two striatal output cells (Reiner et al, 2003;Lei et al, 2004). In light of these data, it is likely that CPn cells preferentially innervate GPe-exclusive cells while CCS cells innervate direct pathway cells.…”
Section: Functional Differentiation Of Corticostriatal Pathwaysmentioning
confidence: 99%
“…Direct pathway cells are considered to promote desired movements, and GPe-exclusive cells are considered to inhibit unwanted movement (Albin et al, 1989;DeLong, 1990;Lei et al, 2004). Recently, it has been revealed that two types of corticostriatal cells differentially innervate one of the above two striatal output cells (Reiner et al, 2003;Lei et al, 2004). In light of these data, it is likely that CPn cells preferentially innervate GPe-exclusive cells while CCS cells innervate direct pathway cells.…”
Section: Functional Differentiation Of Corticostriatal Pathwaysmentioning
confidence: 99%
“…This input primarily ends as terminals that make asymmetric synaptic contact with dendritic spines of striatal projection neurons, which make up ϳ95% of striatal neurons (Albin et al, 1989;Reiner and Anderson, 1990;Gerfen, 1992). In each cortical region, two types of corticostriatal neuron can be distinguished (Wilson, 1987;Cowan and Wilson, 1994;Wright et al, 1999Wright et al, , 2001Reiner et al, 2003). One type, which we refer to as the pyramidal tract (PT)-type, possesses 15-20 m perikarya found primarily in lower layer V, and their striatal projection arises as a collateral of the main axon as it traverses striatum in its course to the ipsilateral pyramidal tract (Wilson, 1987;Cowan and Wilson, 1994;Levesque et al, 1996a,b;Levesque and Parent, 1998;Reiner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In each cortical region, two types of corticostriatal neuron can be distinguished (Wilson, 1987;Cowan and Wilson, 1994;Wright et al, 1999Wright et al, , 2001Reiner et al, 2003). One type, which we refer to as the pyramidal tract (PT)-type, possesses 15-20 m perikarya found primarily in lower layer V, and their striatal projection arises as a collateral of the main axon as it traverses striatum in its course to the ipsilateral pyramidal tract (Wilson, 1987;Cowan and Wilson, 1994;Levesque et al, 1996a,b;Levesque and Parent, 1998;Reiner et al, 2003). The second type projects to basal ganglia and cortex but not outside telencephalon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations